Design of an Affordable Modernized Gate for Kabale University Faculty Of Engineering, Technology, Applied Design & Fine Art. - Angabire, Nicholas (Kabale University, 2023)
The practical work was carried out during my gate design project as far as construction work is concerned. Chapter 1 is the introduction of the proposal that states the contents of the background of the project, how the problem was identified and why the project viable. Chapter 2 contains the literature review, works and related information by other scholars about design mainly architectural working drawings. Chapter 3 outlines the methodology of how the project was done; these are sequential methods for the process. Chapter 4 discusses the results and project discussions that involve details of the budget, work plan, appendices and reference.